2021
DOI: 10.1111/jfpp.16139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermally treated mulberry leaves on the quality, properties, and antioxidant activities of yogurt

Abstract: Mulberry leaf extract (MLE) was used to enhance the functionality of yogurt. Yogurt was fermented with 15% MLE prepared using different thermal treatment methods: no treatment (MY), steamed (SMY), and roasted (RMY). The controls were yogurt with no MLE (Y) and green tea extract (GY). Yogurt acidity was not significantly different among the samples after 8 hr of fermentation. Lactobacilli count was higher in MLE yogurts, with the thermal treatment method not impacting the count. MLE yogurts had high total antho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous research has shown that incorporation of rosehip powder in cookies has definitely increased the total phenolic content [54]. A signif-icant increment of total phenolic content was also observed in nettle-enriched bread [50], beetroot juice-enriched yogurt [55] and mulberry leaf extract-enriched yogurt [56].…”
Section: Total Phenolic Amountmentioning
confidence: 87%
“…Previous research has shown that incorporation of rosehip powder in cookies has definitely increased the total phenolic content [54]. A signif-icant increment of total phenolic content was also observed in nettle-enriched bread [50], beetroot juice-enriched yogurt [55] and mulberry leaf extract-enriched yogurt [56].…”
Section: Total Phenolic Amountmentioning
confidence: 87%
“…The ability of mulberry anthocyanins to scavenge DPPH free radicals was evaluated, following a previously reported method (Wang et al, 2022). In brief, the sample solution was homogenized with 10 mL of ethanol and 0.8 mL of 0.15 mM DPPH.…”
Section: Dpph Assaymentioning
confidence: 99%
“…In this context, Wajs et al ( 6 ) suggested that yoghurts enriched with natural additives are more valuable, particularly with respect to health-promoting constituents’ content, such as phenolic compounds, fibre, essential vitamins, minerals, and fatty acids. Thus, many natural additives, such as date palm spikelets ( 25 ), moringa seed ( 26 ), cornelian cherry paste ( 27 ), grape seeds ( 28 ) and argel leaf ( 29 ) extracts, mulberry leaf and fruit powder ( 30 , 31 ), spearmint and lemongrass essential oils ( 32 ), lentil flour ( 33 ), and different types of fibres ( 34 ), have been incorporated in yoghurt formulation. The benefits of these and many other natural additives, usually added to yoghurt to serve a particular purpose, were discussed in a recent review ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study was set up to investigate the antioxidant, enzymes inhibitory, physicochemical and sensory properties of instant bio-yoghurts containing sweet detar-hibiscus calyx-ginger rhizome blend multi-purpose natural additives. The incorporation of an optimized multi-purpose natural additives blend in the formulation of an instant bio-yoghurt makes this present study unique from the previous studies listed above (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), in which only a particular natural additive was incorporated into yoghurt.…”
Section: Introductionmentioning
confidence: 99%